2012
DOI: 10.1055/s-0032-1313913
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism during Valproic Acid Therapy in Children and Adolescents with Epilepsy

Abstract: The aim of this study was to evaluate the incidence of thyroid dysfunction during valproic acid (VPA) therapy in children and adolescents with epilepsy. The serum levels of thyroid-stimulating hormone (TSH), free thyroxine, and triiodothyronine were evaluated in 61 children with epilepsy who received VPA monotherapy for more than 6 months and in 144 controls. We analyzed the effect of age, seizure type, duration of VPA treatment, dose of VPA, and serum level of VPA on thyroid function. The incidence of subclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 22 publications
(32 reference statements)
2
46
3
Order By: Relevance
“…We include this description of these subjects to avoid the lost to follow-up because of sudden death [22] and the diagnostic bias due to other exposure status. Specifically, patients with known autoimmune diseases [23] or using drugs that may interfere with thyroid function [24,25] are prone to develop autoimmune thyroiditis or subclinical hypothyroidism. Furthermore, 2 subjects refused to continue the study and 3 were lost to follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…We include this description of these subjects to avoid the lost to follow-up because of sudden death [22] and the diagnostic bias due to other exposure status. Specifically, patients with known autoimmune diseases [23] or using drugs that may interfere with thyroid function [24,25] are prone to develop autoimmune thyroiditis or subclinical hypothyroidism. Furthermore, 2 subjects refused to continue the study and 3 were lost to follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies showed an association of age and/or duration of VPA treatment with thyroid hormone imbalance (Mikati et al ., ; Sahu et al ., ), while others have reported opposing results (Tanaka et al ., ; Castro‐Gago et al ., ; Hirfanoglu et al ., ). In addition, significant correlations between the levels of thyroid hormones and VPA daily dosage or serum concentration have been reported (Kim et al ., ).…”
mentioning
confidence: 97%
“…Isojarvi et al (8) reported reduced levels of fT4 in 50-100% of patients on CBZ-VPA. Previous studies reported that polytherapy was associated with SCH (19,23). The altered thyroid function during CBZ medication and been attributed to induction of the hepatic P-450 enzyme system and the consequent increase in the metabolism of thyroid hormones (3)(4)(5)(6)11,37).…”
Section: Discussionmentioning
confidence: 99%